Simulated annealing applied to IMRT beam angle optimization: A computational study - Dias, Joana (2015)
Electing irradiation directions to use in IMRT treatments is one of the first decisions to make in treatment planning. Beam angle optimization (BAO) is a difficult problem to tackle from the mathematical optimization point of view. It is highly non-convex, and optimization approaches based on gradient descent methods will probably get trapped in one of the many local minima. Simulated Annealing (SA) is a local search probabilistic procedure that is known to be able to deal with multimodal problems. SA for BAO was retrospectively applied to ten clinical examples of treated cases of head-and neck tumors signalized as complex cases where proper target coverage and organ sparing proved difficult to achieve. The number of directions to use was considered fixed and equal to 5 or 7. It is shown that SA can lead to solutions that significantly improve organ sparing, even considering a reduced number of angles, without jeopardizing tumor coverage.